Perceptions of meritocracy: A note on China. Issue 2 (June 2019) - Bubak, Oldrich
The last decades have witnessed a number of lapses and contradictions in the outcomes of policy and governance. It is no coincidence there has been an increasing interest from both within and without the academe in alternate systems of selection, representation and accountability, and in revisiting fairness, equity, and social mobility. This article engages a set of beliefs seen as fundamental in the debates and critiques of social systems in general, and of equality of opportunity and outcomes in particular. We thus seek to explore the factors influencing the individual perceptions of merit as opposed to chance as the determinant of success. The focus is on China, a sui generis state with a millennium-long Confucian tradition that continues to influence its meritocratic approach to education and governance. The results indicate a significant departure from the theorized explanations established in Western studies. Notably, we find that higher levels of education are negatively related with the endorsement of meritocracy, or views that effort rather than luck determines individual outcomes. At once, as we study the outlooks of Chinese citizens, we respond to and complement the emerging research with a potential to extend our conceptions of meritocracy in general.